PENGEMBANGAN BAHAN AJAR KEWIRAUSAHAAN DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING DI PROGRAM STUDI PENDIDIKAN AKUNTANSI FKIP UNIVERSITAS PGRI PALEMBANG TAHUN 2014 - Toyib, Muhammad; Martono, Trisno; Sawiji, Hery (Jurnal Pendidikan Insan Mandiri, 2015)
The objectives of research and development were: (1) to formulate the need for entrepreneurship teaching material in Accounting Education Study Program of Teacher Training and Education Faculty (FKIP) of Palembang PGRI University; (2) to develop the entrepreneurship teaching material prototype using contextual teaching and learning; and (3) to obtain a feasible entrepreneurship teaching material with contextual teaching and learning approach to be applied to Accounting Education Study Program of FKIP of Palembang PGRI University.The research method employed research and development model simplified into three steps: preliminary study, model development, and model testing. The preliminary study applied a descriptive qualitative research by means of interview, observation and documentation as the methods of collecting data. The data validation was conducted using method triangulation. The model development step applied quantitative research in both restricted and broad trial. The model testing step applied an experimental research that compared the test result of experiment and control groups. The sample of research included the students of Mathematics Education and Accounting Education Study Programs of FKIP of Palembang PGRI University.The results of research showed: (1) the entrepreneurship learning conducted at college that should be improved through a module with contextual teaching and learning approach; (2) design of module with contextual teaching and learning approach; and (3) the effectiveness of module with contextual teaching and learning approach in improving the students? learning outcome. Implication and recommendation: the use of module with contextual teaching and learning approach could help the students understood the entrepreneurship material because it was equipped with examples, figures, summary, exercise and case study.Keywords: Model Development, CTL, Entrepreneurship Learning, research and development design.